A Mixed Heavier Si=Ge Analogue of a Vinyl Anion. Issue 1 (26th October 2020) - Majhi, Paresh Kumar; Huch, Volker; Scheschkewitz, David
Abstract: The versatile reactivities of disilenides and digermenide, heavier analogues of vinyl anions, have significantly expanded the pool of silicon and germanium compounds with various unexpected structural motifs in the past two decades. We now report the synthesis and isolation of a cyclic heteronuclear vinyl anion analogue with a Si=Ge bond, potassium silagermenide as stable thf‐solvate and 18‐c‐6 solvate by the KC8 reduction of germylene or digermene precursors. Its suitability as synthon for the synthesis of functional silagermenes is proven by the reactions with chlorosilane and chlorophospane to yield the corresponding silyl‐ and phosphanyl‐silagermenes. X‐ray crystallographic analysis, UV/Vis spectroscopy and DFT calculations revealed a significant degree of π‐conjugation between N=C and Si=Ge double bonds in the title compound. Abstract : The first heteronuclear vinyl anion consisting of two heavier Group 14 elements, silagermenide 3 ⋅K(18‐c‐6), is readily accessible by KC8 reduction of a NHC‐stabilized germylene or the corresponding NHC‐free digermene. Its applicability as synthon for the synthesis of unprecedented functional silagermenes 4 a, b and evidence for significant π‐conjugation between the N=C and Si=Ge are also reported.